L

Which expression is equivalent to 5(c + b) + 9b ? 3c?

8 Answers
A.)4b ? 8c b.)14b + 2c c.)14b ? 2c d.)4b + 8c
L

The answer is b.)

You first apply the order of operations on everything: Mult and Div then Add and Subt
So, do all the Mult and Div first. In this case, multiply the 5 over the stuff inside the parenthesis:

5*c + 5*b + 9b - 3c = 5c + 5b + 9b - 3c

Then the the Add and Subt of the matching terms (letters):

Start with the C's: 5c - 3c = 2c
the the B's: 5b + 9b = 14b

Then combine the results: 2c + 14b or 14b + 2c.

Therefore 5(c + b) + 9b ? 3c = 14b + 2c
or choice b.

...
I

5(c+B) + 9b - 3c open the brackets and we get 5c + 5b +9b - 3c

Now simplify the expression

5c - 3c = 2c and 9b + 5b = 14b, or, more correctly c(5-3) + b(5 + 9) we get........

....2c + 14b = answer b!

...
D

Very easy

5(c+b)+9b-3c = 5c + 5b +9b -3c

Now we will group b's and c's together, so it becomes

(5c-3c)+(5b+9b) = 2c+14b

Upon rearranging this, we get

Answer = 14b+2c

...
G

The right answer is b.)14b + 2c

After grouping the c's and b's together, we get

5c -3c +5b +9b

what equals to

2c + 5b +9b

and results in

2c + 14b.

...
A

Simplifying the given expression by distributing and by adding like terms, 5(c + b) + 9b - 3c = 5c + 5b + 9b - 3c = 14b + 2c. Therefore b) option 14b + 2c is equivalent to the given expression.

...
S

The answer is b.) 14b + 2c
Here is the explanation:
5 ( c + b ) + 9b - 3c
= 5c +5b + 9b -3c
= 5c -3c +5b +9b
= 2c + 5b +9b
= 2c + 14b ( Answer: b )

...
W

5(c + b) + 9b ? 3c can be rewritten as:

5c + 5b + 9 b -3c (opening the brackets)

Thus:

14b + 2c

ANSWER B :)

...
A

I'm so stupid! Now I know where to get my homework done without doing it by myself... xD

...